THE EFFECT OF TRAINING AND WORKING FACILITIES TOWARDS CAREER DEVELOPMENT IN THE RESEARCH AND DEVELOPMENT DEPARTMENT OF LABUHAN BATU DISTRICT - Bayu Eko Broto (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2020)
This study aims to determine the effect of educating and training in career development at the Labuhanbatu Regency Research and Development Department, to determine the effect of work facilities in career development at the Labuhanbatu Regency Research and Development Department,. The results showed that educating and training had a positive and significant effect in career development at the Labuhanbatu Regency Research and Development Department, work facilities also had a positive and significant effect on career development in the Labuhanbatu Regency Research and Development Department. The result of multiple regression is Y = 0.143 + 0.179X1 + 0.806X2.